Accumulation of aerosols over the Indo-Gangetic plains and southern slopes of the Himalayas: distribution, properties and radiative effects during the 2009 pre-monsoon season - R. Gautam; N. C. Hsu; S. C. Tsay; K. M. Lau; B. Holben; S. Bell; A. Smirnov; C. Li; R. Hansell; Q. Ji; S. Payra; D. Aryal; et al. (Atmospheric Chemistry and Physics, 2011)
We examine the distribution of aerosols and associated optical/radiative properties in the Gangetic-Himalayan region from simultaneous radiometric measurements over the Indo-Gangetic Plains (IGP) and the foothill/southern slopes of the Himalayas during the 2009 pre-monsoon season. Enhanced dust transport extending from the Southwest Asian arid regions into the IGP, results in seasonal mean (April–June) aerosol optical depths of over 0.6 – highest over Southern Asia. The influence of dust loading is greater over the Western IGP as suggested by pronounced coarse mode peak in aerosol size distribution and spectral single scattering albedo (SSA). Transported dust in the IGP, driven by prevailing westerly airmass, is found to be more absorbing (SSA550 nm<0.9) than the near-desert region in Northwestern (NW) India suggesting mixing with carbonaceous aerosols in the IGP. On the contrary, significantly reduced dust transport is observed over eastern IGP and foothill/elevated Himalayan slopes in Nepal where strongly absorbing haze is prevalent, as indicated by lower SSA (0.85–0.9 at 440–1020 nm), suggesting presence of more absorbing aerosols compared to IGP. Additionally, our observations show a distinct diurnal pattern of aerosols with characteristic large afternoon peak, from foothill to elevated mountain locations, associated with increased upslope transport of pollutants – that likely represent large-scale lifting of absorbing aerosols along the elevated slopes during pre-monsoon season. In terms of radiative impact of aerosols, over the source region of NW India, diurnal mean reduction in solar radiation fluxes was estimated to be 19–23 Wm−2 at surface (12–15% of the surface solar insolation). Furthermore, based on limited observations of aerosol optical properties during the pre-monsoon period and comparison of our radiative forcing estimates with published literature, there exists a general spatial heterogeneity in the regional aerosol forcing, associated with the absorbing aerosol distribution over northern India, with both diurnal mean surface forcing and forcing efficiency over the IGP exceeding that over Northwestern India. Finally, the role of the seasonal progressive buildup of aerosol loading and water vapor is investigated in the observed net aerosol radiative effect over Northwestern India. The radiative impact of water vapor is found to amplify the net regional aerosol radiative forcing suggesting that the two exert forcing in tandem leading to enhanced surface cooling. It is suggested that water vapor contribution should be taken into account while assessing aerosol forcing impact for this region and other seasonally similar environments.